Analysis of Political Communication of Party Wing Organizations through the Facebook Account @DPPBantengMudaIndonesia in Constructing a Positive Image of PDI Perjuangan After the 2024 Election - Rheshinta Wibawani Pujantari; Restu Rahmawati (Department of Government Studies, Faculty of Social and Political Sciences, Universitas Syiah Kuala, 2026)
This study aims to analyze the political communication of a party wing organization through the Facebook account @DPPBantengMudaIndonesia in building a positive image of PDI Perjuangan after the 2024 General Election. Using a qualitative method with a netnographic approach, the research explores communication patterns, forms of political messages, and audience responses in the digital sphere. Data were obtained through digital observation of posts, comments, and user interactions on the account, supported by interviews and literature review. The analysis applies Harold D. Lasswell’s communication theory, emphasizing the framework of “who says what in which channel to whom with what effect.” The findings show that BMI acts as a digital political communicator consistently reinforcing PDI Perjuangan’s image through humanitarian content, organizational agendas, ideological symbols, and narratives of closeness with society. BMI’s communication activities are directly associated by the public with PDI Perjuangan as the main party. Audience responses reveal a dominance of positive sentiment, particularly increased engagement with social and humanitarian content.This study highlights the strategic role of party wing organizations in strengthening political legitimacy and constructing a positive party image through social media. In the digital era, BMI functions not only as a vehicle for cadre recruitment but also as a medium of representation, legitimacy, and image consolidation for PDI Perjuangan.